Effect of E-Archive Utilization on Work Performance and Productivity: The Moderating Effect of Study Quality Systems in Malang’s State Universities - Azzuhri, Fahmi Muhammad; Permanasari, Kartika Indah; Iqbal, Muhammad; Sinartya, Jatrifia Ongga (Universitas Negeri Makassar, 2025)
This study aims to analyze the effect of e-Archive system utilization on the performance and work productivity of educational staff at state universities in Malang City, with quality systems serving as a moderating variable. Data were collected through questionnaires distributed to academic administrative staff from three state universities in Malang. The analysis employed Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The findings reveal that the utilization of e-Archive systems has a significant positive effect on improving work performance and productivity. Furthermore, the quality system strengthens the relationship between e-Archive utilization and employee performance improvement. These results highlight the importance of digital document management that is not only technically efficient but also supported by a consistent quality system and responsive service delivery.